Intertemporal commitment problems and voting on redistributive taxation - Amihai Glazer; Kai A. Konrad (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
A rich person who fears a loss of income may later favor redistributive taxation and a mix of taxes and public goods that differs from the one he now favors. If mobility is costly, and if government in each period uses majority voting to determine policy, then this person may prefer to live in a community that is permanently ruled by poor residents. Majority voting is a mechanism that can overcome intertemporal commitment problems of income insurance.
Keywords: 330